Glycogen synthase kinase-3β inhibitor ameliorates imbalance of connexin 43 in an acute kidney injury model. (2015) - Wang, Yini; Tong, Ke
Abstract: This study was designed to evaluate whether glycogen synthase kinase-3β (GSK-3β) inhibitor, 4-benzyl-2-methyl-1, 2, 4-thiadiazolidine-3, 5-dione (TDZD-8) induced the the expression of connexin 43 (Cx43) to protect against renal ischemia–reperfusion (I/R) injury (RI/RI) in rats. Rats were subjected to 45 min ischemia followed 2 h reperfusion with TDZD-8 (1 mg/kg) for 5 min prior to reperfusion. The results indicated that TDZD-8 improved the recovery of renal function, reduced oxidative stress and inflammation injury, and upregulated the expression of (Cx43) as compared to I/R group. Therefore, our study demonstrated that TDZD-8 provided a protection to the kidney against I/R injury in rats through inducing the expression of (Cx43).